Comparison Of Durability Between Uv Inkjet And Conventional Offset Prints Exposed To Accelerated Ageing - Karlovits, Mirica; Gregor-Svetec, Diana (Journal of Graphic Engineering and Design, 2023)
The present study deals with the optical and colour stability of aged offset and UV inkjet prints. As a paper substrate, a film synthetic paper was used, which was printed by two techniques (UV inkjet press Óce Arizona 250® GT and conventional offset press KBA Performa 74). Film synthetic paper, offset prints and UV inkjet prints were artificially aged using standard techniques of accelerated ageing, such as moist-heat (80 °C and 65% relative humidity) and dry-heat (105 °C). Ageing was performed for periods of 1, 2, 3, 6 and 12 days. It was found that the moist-heat accelerated ageing influenced the most on optical properties of film synthetic paper. UV inkjet prints had higher colourfastness than the conventional offset prints. The most stable among all tested prints was the black colour UV inkjet print.